2015
DOI: 10.1007/s11695-015-1735-2
|View full text |Cite
|
Sign up to set email alerts
|

Sleeve Gastrectomy in Different Age Groups: a Comparative Study of 5-Year Outcomes

Abstract: LSG is a useful tool for people who want to modify their eating habits and lose weight healthily. This study suggests that long-term weight loss, improvements in comorbidity, and compliance to follow-up are significant for patients >55 years old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 44 publications
1
8
0
5
Order By: Relevance
“…Consistent with the present findings, a study by Charalampakis et al [16] found an improved MAQOL within 24 months after LSG. In the present study there was no influence of gender and age on the improvement of MAQOL, which is in line with current literature [26]. Confirming patients’ expectations and goals, obesity surgery led to a reduction of comorbidities in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the present findings, a study by Charalampakis et al [16] found an improved MAQOL within 24 months after LSG. In the present study there was no influence of gender and age on the improvement of MAQOL, which is in line with current literature [26]. Confirming patients’ expectations and goals, obesity surgery led to a reduction of comorbidities in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The benefit of LSG in terms of HRQOL improvement was also proven in older patients > 55 years of age, which interestingly was even higher than in younger groups [39][40]. Both studies also showed safety of this procedure in older patients.…”
Section: Discussionmentioning
confidence: 69%
“…According to the fifth International Federation for the Surgery of Obesity and metabolic disorders (IFSO) 2019 report, 305 242 LSG procedures were performed during 2015‐2018, 1 accounting for 58.6% of all bariatric procedures. Studies with long term follow‐up have reported an excess weight loss varying from 40% to 57% 2‐4 . Inadequate weight loss and weight regain following LSG remains a concern especially with the high number of surgeries being performed.…”
Section: Introductionmentioning
confidence: 99%